Maternal High-Fat Diet Programs Offspring Liver Steatosis in a Sexually Dimorphic Manner in Association with Changes in Gut Microbial Ecology in Mice - Umesh D. Wankhade (Nature Portfolio, 2018)
Abstract The contributions of maternal diet and obesity in shaping offspring microbiome remain unclear. Here we employed a mouse model of maternal diet-induced obesity via high-fat diet feeding (HFD, 45% fat calories) for 12 wk prior to conception on offspring gut microbial ecology. Male and female offspring were provided access to control or HFD from weaning until 17 wk of age. Maternal HFD-associated programming was sexually dimorphic, with male offspring from HFD dams showing hyper-responsive weight gain to postnatal HFD. Likewise, microbiome analysis of offspring cecal contents showed differences in α-diversity, β-diversity and higher Firmicutes in male compared to female mice. Weight gain in offspring was significantly associated with abundance of Lachnospiraceae and Clostridiaceae families and Adlercreutzia, Coprococcus and Lactococcus genera. Sex differences in metagenomic pathways relating to lipid metabolism, bile acid biosynthesis and immune response were also observed. HFD-fed male offspring from HFD dams also showed worse hepatic pathology, increased pro-inflammatory cytokines, altered expression of bile acid regulators (Cyp7a1, Cyp8b1 and Cyp39a1) and serum bile acid concentrations. These findings suggest that maternal HFD alters gut microbiota composition and weight gain of offspring in a sexually dimorphic manner, coincident with fatty liver and a pro-inflammatory state in male offspring.